2018
DOI: 10.1021/acs.jpcc.8b08412
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Density-Functional Theory Calculations of Electronic and Optical Properties of Mercaptocarboxylic Acids on ZnO(101̅0) Surfaces

Abstract: In this work we investigate the electronic properties of mercaptocarboxylic acids with several carbon chain lengths adsorbed on ZnO-(10-10) surfaces via density functional theory calculations using semi-local and hybrid exchange-correlation functionals.Amongst the investigated structures, we identify the monodentate adsorption mode to be stable. Moreover, this mode introduces optically active states in the ZnO gap, is further confirmed by the calculation of the dielectric function at PBE0 and TD-PBE0 levels. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
1
1
Order By: Relevance
“…Functionalization with thiol groups resulted in the appearance of intra-gap molecular states. However, in contrast to thiol groups on previously investigated ZnO surfaces [31], these states are not optically active, probably leading to hole trapping. Further investigations on more realistic surfaces including perhaps the presence of hydroxyl groups and defects are needed to suggest whether and how surface modification can enhance the optical properties of GaN.…”
Section: Discussioncontrasting
confidence: 62%
“…Functionalization with thiol groups resulted in the appearance of intra-gap molecular states. However, in contrast to thiol groups on previously investigated ZnO surfaces [31], these states are not optically active, probably leading to hole trapping. Further investigations on more realistic surfaces including perhaps the presence of hydroxyl groups and defects are needed to suggest whether and how surface modification can enhance the optical properties of GaN.…”
Section: Discussioncontrasting
confidence: 62%
“…Earlier studies of the interactions of primary carboxylic and mercapto-carboxylic acids 40,41 with zeolites and ZnO surfaces have shown that adsorption modes and dielectric properties of the hybrid systems are rather insensitive to the chain length, since the interaction state is localised on the specific atom (either carboxyl oxygen or mercapto-sulphur). Structural and electronic properties of OA, as the experimental compound of interest, and VA, as a segment of OA cut at the fourth carbon atom of the alkyl chain where the distance from the carboxyl group is larger than three bonds thus diminishing the inductive effect, have been compared by DFT calculations using the computational details specified in Section 2.1.…”
Section: Choice Of Carboxylic Acidmentioning
confidence: 99%